Analysis of Water Pollution Index in The Tributary of Kusan River, South Kalimantan - Nurkhaerani, Fatma; Adzillah, Wilma Nurrul; Sari, Gina Lova; Oktariyanto, Eka Nugroho (Jurnal Teknik Sipil dan Lingkungan, 2025)
Domestic wastewater discharge remains a major factor contributing to the deterioration of river water quality, as untreated effluents are still commonly released directly into river systems. This concern is particularly evident in the downstream segment of the Kusan River tributary, situated in the villages of Sungai Lembu and Beringin. The intensifying expansion of residential settlements in the area has been identified as a key driver of pollution in the Kusan River, with its scale increasing annually. Environmental degradation arises when the pollutant load exceeds the assimilative capacity of the aquatic ecosystem. Under such conditions, the natural recovery process becomes protracted and increasingly ineffective, resulting in persistent contamination. This research is designed to assess the influence of surrounding anthropogenic activities on the water pollution index and the ecological condition of the Kusan River tributary in the aforementioned villages, within Tanah Bumbu Regency, South Kalimantan Province, employing the Water Pollution Index (WPI) methodology. Based on laboratory analyses, Total Suspended Solids (TSS) concentrations in the lower reaches of the tributary exceed 50 mg/L, thus surpassing the threshold set by Government Regulation No. 22 of 2021 concerning Water Quality Management and Pollution Control. Moreover, findings from the pollution index evaluation indicate that water quality in the study area ranges from good to lightly polluted, with index scores varying between 0.33 and 1.73.